2001
DOI: 10.1207/s15326942dn2003_7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Control Across the Life Span

Abstract: Findings from previous research suggest that inhibitory control improves during early childhood and declines during late adulthood. Very few researchers, however, have examined life-span changes in this ability in single studies. Within this life-span context, we investigated 1 type of inhibitory control--the ability to inhibit aprepotent response and generate an incompatible response--in individuals ranging from 6 to 82 years of age. Examination of raw reaction time data revealed a significantly larger inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(68 citation statements)
references
References 50 publications
3
61
0
4
Order By: Relevance
“…After controlling for processing speed, only the effect of age on working memory remained significant. These results are consistent with previous work showing that processing speed, response inhibition, and working memory have a protracted course of development (e.g., Kail, 1991; Jerger, Pearson, & Spence, 1999; Luna, Garver, Urban, Lazar, & Sweeny, 2004 ; Williams et al; 1999; Wright, Waterman, Prescott, & Murdoch-Eaton, 2003) and that age-related improvements in these latter abilities are ameliorated once age-related improvements in processing speed are taken into account (e.g., Christ et al, 2001; Fry & Hale, 1996; Span et al, 2004). …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…After controlling for processing speed, only the effect of age on working memory remained significant. These results are consistent with previous work showing that processing speed, response inhibition, and working memory have a protracted course of development (e.g., Kail, 1991; Jerger, Pearson, & Spence, 1999; Luna, Garver, Urban, Lazar, & Sweeny, 2004 ; Williams et al; 1999; Wright, Waterman, Prescott, & Murdoch-Eaton, 2003) and that age-related improvements in these latter abilities are ameliorated once age-related improvements in processing speed are taken into account (e.g., Christ et al, 2001; Fry & Hale, 1996; Span et al, 2004). …”
Section: Discussionsupporting
confidence: 92%
“…Consistent with this notion, there is a growing body of evidence showing that processing speed mediates gains in other cognitive abilities – including those that are subsumed under the rubric of executive function (Christ et al, 2001; Fry & Hale, 1996; Kail, 2007; Nettlebeck & Burns, 2010; Span et al, 2004). In the context of our cross-sectional study, we found that processing speed accounted for considerable variance in working memory and response inhibition across development.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Inhibitory control, assessed with measures other than the Stroop (e.g., Stop signal), also shows a protracted development from childhood to adulthood (Williams et al, 1999; Bedard et al, 2002; Davidson et al, 2006), although some suggest it develops very early (by grade 2; Schachar and Logan, 1990; Christ et al, 2001). It appears, however, that the rate at which inhibition develops changes as a function of age (Luna and Sweeney, 2004; Best et al, 2009; for reviews).…”
Section: Introductionmentioning
confidence: 99%
“…The latter concern has been addressed to some extent. In a well examined sample, Christ and colleagues (Christ et al, 2001; McAuley et al, 2006) addressed this concern and established that the inhibitory deficit in the older participants could not be explained by response slowing. They went on to show with ex-Gaussian analysis that inhibitory limitations in older adults differed in quality from those in children.…”
mentioning
confidence: 99%